2014
DOI: 10.3389/fncir.2014.00106
|View full text |Cite
|
Sign up to set email alerts
|

Swimming against the tide: investigations of the C-bouton synapse

Abstract: C-boutons are important cholinergic modulatory loci for state-dependent alterations in motoneuron firing rate. m2 receptors are concentrated postsynaptic to C-boutons, and m2 receptor activation increases motoneuron excitability by reducing the action potential afterhyperpolarization. Here, using an intensive review of the current literature as well as data from our laboratory, we illustrate that C-bouton postsynaptic sites comprise a unique structural/functional domain containing appropriate cellular machiner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(118 citation statements)
references
References 198 publications
(305 reference statements)
6
112
0
Order By: Relevance
“…With the emergence of new data about the C-bouton structure and function, and its possible relevance to MN pathology, there has been considerable recent interest in this type of synapses1948. Here, we extend our previous report showing that the NRG1-ErbB2/3 signalling module is expressed at C-boutons18, by providing a more detailed analysis of the compartmentation of these molecules and their relation with other proteins that are known to be specifically clustered at this synaptic site.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…With the emergence of new data about the C-bouton structure and function, and its possible relevance to MN pathology, there has been considerable recent interest in this type of synapses1948. Here, we extend our previous report showing that the NRG1-ErbB2/3 signalling module is expressed at C-boutons18, by providing a more detailed analysis of the compartmentation of these molecules and their relation with other proteins that are known to be specifically clustered at this synaptic site.…”
Section: Discussionsupporting
confidence: 60%
“…We have also demonstrated that ErbB2 and ErbB4 receptors are present in the presynaptic compartment, suggesting that NRG1 acts as a retrograde signalling molecule in C-type synapses. C-boutons are scarcely investigated structures19, which have been reported to suffer plastic changes in sick MNs after spinal cord injury2021, peripheral nerve lesion22, and amyotrophic lateral sclerosis (ALS)1823242526272829. In addition, mutations in S1R are considered risk factors for familial ALS, and abnormal accumulations of this protein in C-terminals have also been observed in patients with sporadic ALS303132.…”
mentioning
confidence: 99%
“…; Deardorff et al . ). We next analysed action potential waveform parameters during repetitive firing for evidence of Na + channel inactivation.…”
Section: Resultsmentioning
confidence: 97%
“…; Liu & Bean, ) and on their precise subcellular somato‐dendritic localization (Muennich & Fyffe, ; Deardorff et al . ). Kv2 subunits, in particular, are widely expressed throughout the mammalian brain and spinal cord (Trimmer, ; Scannevin et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation